Prevention of wound infection: a new technique - Kumar, Mahendra; Pawar, Preeti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean delivery is a major obstetrical surgical procedure aiming to save the lives of mothers and fetuses. Caesarean sections have a 5 to 20-fold greater chance of getting an infection compared with women who give birth vaginally. These infections can be in the organs within the pelvis, around the surgical incision. Microorganisms isolated from surgical site infection (SSI) were mostly from skin and vaginal flora. The most effective SSI prevention strategies involve a multi-faceted approach including protocols exercised before, during, and after surgery to reduce exposure and susceptibility to pathogens. Methods: It was a case control study conducted in our hospital on caesarean patients. Total 240 patients were recruited for study, divided into cases (DDT group) and control (SDT group). Demographic data collected and follow till 30 days of surgery. SSIs patients identified and treated. Results: Out of total 240 patients, mean age SDT, DDT and total patients were 28.46, 28.6 and 28.3 years respectively. Maximum numbers of cases were among multigravida (gravidity) and lower and lower-middle class (socioeconomic status). SSIs patients were seen mostly in SDT group, which was statistically significant. Among SSIs patient maximum numbers of patients were seen in age group of 18-22 years, primigravida and lower socioeconomic class. After their diagnosis most of the patients were treated with resuturing. Conclusions: SSI is common complication after caesarean section; it can be prevented by increasing the hygienic condition in laboring patients. Authors newer method can be a future option for maintaining the intraoperative hygiene.